PERSEPSI PASIEN RAWAT INAP TERHADAP KINERJA RSUD WANGAYA - I Made Suardi Kesuma (Jurnal Manajemen dan Bisnis, 2013)
Excellent service is an important elemen in the quality of service that in hospital.withgiving satisfaction to the hospital ,as well as in regional pablic hospital wangaya .a hospitalthe dutch pride is expected to provide the best service for statisfation of patien.With hope complacence patiens aciped,the patiens expect interaktion both to serviceprovider ,namely the Docters,nurses and labour non medis.althoug so satisfied patiensresulting in incresed hospital performance.Respondents research these are hospitalized patiens to guarantee access of beingtrated in Rumah Sakit Umum Daerah Kota Denpasar the dutch 125 patients.with the fouevariabel influance positif significan and positive insignifinat are two variabel.Keywords : Service quality,satisfaction and performances.